1995
DOI: 10.2134/jpa1995.0501
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Major Dairy Forage Systems in Pennsylvania: The Role of Intensive Grazing

Abstract: The economic impact of intensive grazing for a representative Pennsylvania Holstein (Bos taurus) dairy farm was evaluated using a Monte‐Carlo farm level simulation model. Ten harvested forage combinations with or without intensive grazing of pasture were modeled. For each of 10 farm scenarios, least‐cost rations were developed to meet the requirements for the level of milk production. Net cash farm income, and the after‐tax net present value of ending net worth were used as profitability measures. The after‐ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Ration ingredients and prices for all feeds (Table 1) Table 2) (Rasmussen, 2003). Pasture costs were derived from Elbehri and Ford (1995) and were estimated to be $0.0482/kg DM grown. The cost data of Elbehri and Ford (1995) are older than that of the output prices.…”
Section: Economic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ration ingredients and prices for all feeds (Table 1) Table 2) (Rasmussen, 2003). Pasture costs were derived from Elbehri and Ford (1995) and were estimated to be $0.0482/kg DM grown. The cost data of Elbehri and Ford (1995) are older than that of the output prices.…”
Section: Economic Informationmentioning
confidence: 99%
“…Pasture costs were derived from Elbehri and Ford (1995) and were estimated to be $0.0482/kg DM grown. The cost data of Elbehri and Ford (1995) are older than that of the output prices. However, those data were used because more contemporary data were not available.…”
Section: Economic Informationmentioning
confidence: 99%
“…The Minnesota and Mississippi studies found pasture‐based systems to economically outperform conventional systems; the North Carolina study found that pasture‐based systems could be competitive with conventional systems under certain conditions; and the Pennsylvania study found higher economic performance with conventional systems. Analyses using simulation or linked spreadsheet analyses have included Parker et al (1992) in Pennsylvania; Elbehri and Ford (1995) in Pennsylvania; and Soder and Rotz (2001) in Pennsylvania; all of which found favorable economic performance of pasture‐based relative to conventional farms. A third category of studies has compared the systems based upon farm survey results: Hanson et al (2004) in Pennsylvania and Dartt et al (1999) in Michigan, both of which found favorable economic performance of pasture‐based relative to conventional farms.…”
Section: Introductionmentioning
confidence: 99%
“…T he number of pasture ‐ based dairy operations in the lower Midwest has increased four‐fold since 1998 (Pierce et al, 2002). These operations seek to maximize profitability by minimizing input costs while maintaining economic levels of milk production (Elbehri and Ford, 1995; Hanson et al, 1998). One characteristic common to pasture‐based dairy operations in this region is their reliance on high quality pasture instead of hay or silage.…”
mentioning
confidence: 99%